2022
DOI: 10.1093/jxb/erac232
|View full text |Cite
|
Sign up to set email alerts
|

The membrane associated NAC transcription factors ANAC060 and ANAC040 are functionally redundant in the inhibition of seed dormancy inArabidopsis thaliana

Abstract: The NAC family of transcription factors is involved in plant development and various biotic and abiotic stresses. The Arabidopsis thaliana ANAC proteins ANAC060, ANAC040 and ANAC089 are highly homologous based on protein and nucleotide sequence similarity. These three genes are predicted to be membrane bound transcription factors (MTFs) containing a conserved NAC domain but divergent C-terminal regions. The anac060 mutant shows increased dormancy levels when compared to wild type. Mutations in ANAC040 lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…DOG6 encodes the NAC transcription factor ANAC60 ( Song et al 2021 , 2022 ). Different natural alleles of DOG6 determine the localization of the protein due to the presence or absence of a membrane binding domain.…”
Section: The Power Of Natural Variation Among Others a Dog1 Storymentioning
confidence: 99%
“…DOG6 encodes the NAC transcription factor ANAC60 ( Song et al 2021 , 2022 ). Different natural alleles of DOG6 determine the localization of the protein due to the presence or absence of a membrane binding domain.…”
Section: The Power Of Natural Variation Among Others a Dog1 Storymentioning
confidence: 99%
“…Additionally, in mm, “seed germination” function included nine genes inhibiting germination and 10 genes promoting it, e.g., NAC040 (Supplemental Fig. S5A; Supplemental Table S7) (Song et al, 2022). Notably, GmNAC040 was active from reserve accumulation throughout imbibition, whereas AtNAC040 was active during germination only, highlighting their divergent expression patterns (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With the completion of the genome sequencing of lotus root, several gene families were identified [ 44 , 47 , 53 ]. NAC proteins have diverse functions and play vital roles in plant growth and development, including responses to biotic and abiotic stresses [ 14 , 17 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. However, functional research of lotus NAC genes has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%